HSP70 Modulators for the Correction of Cognitive, Mnemonic, and Behavioral Disorders After Prenatal Hypoxia - Aliyeva, O. H.; Belenichev, I. F.; Bilai, I. M.; Duiun, I. F.; Makyeyeva, L. V.; Oksenych, V.; Kamyshnyi, O.; Алієва, Олена Геннадіївна; Бєленічев, Ігор Федорович; Білай, Іван Михайлович; Дуюн, Ірина Федорівна; Макєєва, Людмила Валеріївна (My University, 2025)
Prenatal hypoxia (PH) is a leading cause of nervous system disorders in early childhood and subsequently leads to a decline in the cognitive and mnemonic functions of the central nervous system (such as memory impairment, reduced learning ability, and information processing). It also increases anxiety and the risk of brain disorders in adulthood. Compensatory–adaptive mechanisms of the mother– placenta–fetus system, which enhance the fetus’s CNS resilience, are known, including the activation of endogenous neuroprotection in response to hypoxic brain injury through the pharmacological modulation of HSP70. Methods: To evaluate the effect of HSP70 modulators—Cerebrocurin, Angiolin, Tamoxifen, Glutaredoxin, Thiotriazoline, and HSF-1 (heat shock factor 1 protein), as well as Mildronate and Mexidol—on the motor skills, exploratory behaviors, psycho-emotional activities, learning, and memories of offspring after PH. Experimental PH was induced by daily intraperitoneal injections of sodium nitrite solution into pregnant female rats from the 16th to the 21st day of pregnancy at a dose of 50 mg/kg. The newborns received intraperitoneal injections of Angiolin (50 mg/kg), Thiotriazoline (50 mg/kg), Mexidol (100 mg/kg), Cerebrocurin (150 μL/kg), L-arginine (200 mg/kg), Glutaredoxin (200 μg/kg), HSF-1 (50 mg/kg), or Mildronate (50 mg/kg) for 30 days. At 1 month, the rats were tested in the open field test, and at 2 months, they were trained and tested for working and spatial memory in the radial maze. Results: Modeling PH led to persistent impairments in exploratory activity, psycho-emotional behavior, and a decrease in the cognitive–mnestic functions of the CNS. It was found that Angiolin and Cerebrocurin had the most pronounced effects on the indicators of exploratory activity and psycho-emotional status in 1-month-old animals after PH. They also exhibited the most significant cognitive-enhancing and memory-supporting effects during the training and evaluation of skill retention in the maze in 2-month-old offspring after PH. Conclusions: for the first time, we obtained experimental data on the effects of HSP70 modulators on exploratory activity, psycho-emotional behavior, and cognitive–mnestic functions of the central nervous system in offspring following intrauterine hypoxia. Based on the results of this study, we identified the pharmacological agents Angiolin and Cerebrocurin as promising neuroprotective agents after perinatal hypoxia.
Keywords: prenatal hypoxia; HSP70 modulators; open field test; cognitive disorders; memory disorders; behavioral disorders